Settlement and labour force outcomes for Afghan immigrants and their children in Canada - Ravi Pendakur (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
Past research suggests that Afghan immigrants and their children face challenges in settlement, stemming from the impact of displacement, language barriers, poor health, limited education, limited knowledge of or access to services, and discrimination. Using data from Canada's 2011 National Household Survey and 2009 Longitudinal Immigration Database, this paper adds to these findings, pointing to poor labour force outcomes for most Afghan immigrants as compared to other immigrants. Home ownership probabilities are found to be concomitantly poor. Sons of Afghan immigrants fare better than their fathers, but no better than other immigrant men. However, the daughters of Afghan immigrants fare much better both in terms of employment probabilities and earnings as compared to other immigrant women.
Keywords: J15; 330; Afghan immigrants; Canada; labour force participation; housing tenure